The Narrow‐Clawed Crayfish Pontastacus leptodactylus : Biology, Culture Development, and Prospects for Sustainable Aquaculture - Ardavan Farhadi; Muzaffer Mustafa Harlıoğlu; Erchao Li (Reviews in Aquaculture, 2026)
Pontastacus leptodactylus is a freshwater crayfish native to the Ponto‐Caspian region, with a distribution across Eastern Europe and Western Asia. This review synthesizes current knowledge on the biology, culture development, and prospects for sustainable aquaculture of P. leptodactylus . Commercial exploitation of P. leptodactylus has a long history in Western Europe and the Ponto‐Caspian region and has relied primarily on capture fisheries. Türkiye served as the principal exporter to international markets until the 1985 outbreak of crayfish plague ( Aphanomyces astaci ), which precipitated widespread stock collapses. In contrast, aquaculture development remained limited for decades and has only recently gained momentum, particularly, in China. Following the first identification of P. leptodactylus in China in 2021, interest in its culture has increased, with pilot‐scale farming trials and localized hatchery activities reported across several provinces. However, production remains limited in scale, and these developments are best regarded as early‐stage or proof‐of‐concept initiatives rather than established commercial aquaculture. Accordingly, this review provides an integrated appraisal of culture practices, including broodstock management, artificial incubation, juvenile feeding, stocking strategies, grow‐out systems, and health and biosecurity protocols. It further synthesizes market dynamics, value‐chain development, and welfare considerations alongside performance benchmarks. Key constraints such as the lack of species‐specific feeds, limited tools for cannibalism mitigation, and the absence of selective breeding programs are identified as major barriers to sustainable scale‐up. This review offers a framework to guide future research, management decisions, and aquaculture development for the sustainable utilization of P. leptodactylus .